Mass Media Variables for Anticipating Creativity among Academically Bright Rural Adolescents - Sheoran, Sumit; Dhanda, Bimla; Malik, Joginder Singh (Indian Journal of Extension Education, 2021)
Creativity is the tendency to generate ideas, alternatives and possibilities that may assist in encountering day to day life problems, communicating with others and entertaining ourselves and others whereas media technologies act as a medium while interacting with a large group of audience via mass communication. The study explored the relationship between mass media use and creativity. The primary data collected from 300 participants included independent variables related to mass media used, time spend and the social media use. Five aspects of creativity i.e., seeing problem, unusual uses fluency, unusual uses flexibility, unusual uses originality and unusual uses creativity were used. Chi-square analysis indicated that social media use was significantly associated with the all aspects of unusual uses of creativity of respondents’ i.e., fluency, flexibility, originality and creativity. It was elucidated that the amount of time spend on mass media was significantly associated with adolescents’ seeing problem abilities and their unusual uses fluency. No association was observed between type of mass media used by participants and their creative abilities.
Keywords: Mass media; Young adolescents; Creativity; Academically bright